Matrix mean squared error comparisons of some biased estimators with two biasing parameters. Issue 8 (18th April 2018) - Kurnaz, Fatma Sevinç; Akay, Kadri Ulaş
ABSTRACT: To deal with multicollinearity problem, the biased estimators with two biasing parameters have recently attracted much research interest. The aim of this article is to compare one of the last proposals given by Yang and Chang (2010 ) with Liu-type estimator (Liu2003 ) and k − d class estimator (Sakallioglu and Kaciranlar2008 ) under the matrix mean squared error criterion. As well as giving these comparisons theoretically, we support the results with the extended simulation studies and real data example, which show the advantages of the proposal given by Yang and Chang (2010 ) over the other proposals with increasing multicollinearity level.